Online Learning Problems and the Principal’s Efforts to Overcome the Problems - Lukman Asha (Al-Ishlah: Jurnal Pendidikan, 2021)
The spread of the Coronavirus (Covid-19) has brought various drastic changes to human life, one of which is the mode of learning that should be transformed into an online mode. However, the complexities of online learning leave some problems. Thus, this qualitative study aimed to investigate the online learning processes, problems, and the principal’s solutions at MA Muhammmadiyah Kampung Delima, Rejang Lebong, Bengkulu Province. The principal and five selected teachers were involved as the participants. The data were garnered from interviews and observations, and the data were further analyzed using an interactive model. The findings demonstrated that the school, in general, had implemented online learning processes based on the school and teachers’ existing and general competencies. However, there were some problems therein, including ineffective delivery of materials, inadequate technological facilities of students, students’ lack of discipline, and unstable internet networks. To overcome such problems, the principal arranged assistance from the government to benefit from online learning and actively encouraged teachers to establish communication with parents. As an implication, the curricular contents of teacher education in the Indonesian context should be more sensitive to the discourse of TPACK. Further studies are expected to work on the principal’s managerial role in online learning by involving the principles from various schools.